Is there a general closed form or the integral representation for the limit of the sequence: $$a_{n+1}=\frac{\sqrt{(a_n+b_n)(a_n+c_n)}}{2} \\ b_{n+1}=\frac{\sqrt{(b_n+a_n)(b_n+c_n)}}{2} \\ c_{n+1}=\frac{\sqrt{(c_n+a_n)(c_n+b_n)}}{2}$$ in terms of $a_0,b_0,c_0$?

$$L(a_0,b_0,c_0)=\lim_{n \to \infty}a_n=\lim_{n \to \infty}b_n=\lim_{n \to \infty}c_n$$

For the most simple case $a_0=b_0$ we have some interesting closed forms in terms of inverse hyperbolic or trigomonetric functions:


$$L(1,1,1/\sqrt{2})=\frac{2 \sqrt{2}}{\pi}$$


$$L(1,1,1/2)=\frac{3 \sqrt{3}}{2 \pi }$$


$$L(1,1,1/3)=\frac{2 \sqrt{2}}{3 \arcsin \left( \frac{2 \sqrt{2}}{3} \right)}$$

$$L(1,1,\sin 1)=\frac{2 \cos 1}{\pi -2}$$

$$L(1,1,\sin 1/2)=\frac{2 \cos 1/2}{\pi -1}$$

$$L(1,1,\cosh 1)=\sinh 1$$

$$L(1,1,\cosh 2)=\frac{\sinh 2}{2}$$

These values are obtained by Wolfram Alpha and Inverse Symbolic Calculator and checked with Mathematica.

This result seems familiar to me, but I'm pretty sure I don't know how to obtain a general closed form or even integral representation.

This question is closely related, but the sequence is very different.


It seems likely that the closed form for the special case $a_0=b_0=1$ is:

$$L(1,1,x)=\frac{\sinh \left(\cosh ^{-1}\left(x\right)\right)}{\cosh ^{-1}\left(x\right)}$$

However, the proof would be nice as well as the more general case.

Thanks to Sangchul Lee I now see that this sequence is exactly Carlson's transformation. Change:

$$a^2=A,\quad b^2=B,\quad c^2=C$$

$$A_{n+1}=\frac{1}{4} (A_n+\sqrt{A_nB_n}+\sqrt{B_nC_n}+\sqrt{C_nA_n})$$

$$B_{n+1}=\frac{1}{4} (B_n+\sqrt{A_nB_n}+\sqrt{B_nC_n}+\sqrt{C_nA_n})$$

$$C_{n+1}=\frac{1}{4} (C_n+\sqrt{A_nB_n}+\sqrt{B_nC_n}+\sqrt{C_nA_n})$$

Accoding to Wikipedia and references wherein, we have:


$$R_F(A,B,C)=\frac{1}{2} \int_0^\infty \frac{dt}{\sqrt{(t+A)(t+B)(t+C)}}$$

Which is exactly the 'closed form' I wanted.

  • $\begingroup$ squaring and adding the constituents gives after a parametrization in polar coordinates an interesting constraint namely $1=\sin(\phi_n)\sin(\theta_n)\cos(\phi_n)+\sin(\phi_n)\cos(\theta_n)\cos(\phi_n)+\sin(\phi_n)\sin(\theta_n)\sin(\phi_n)\cos(\theta_n)$ $\endgroup$ – tired Jan 23 '17 at 21:34
  • 1
    $\begingroup$ @tired, So, this would allow us to get rid of two variables and leave only one? $\endgroup$ – Yuriy S Jan 23 '17 at 23:32
  • $\begingroup$ yes indeed!$\quad$ $\endgroup$ – tired Jan 24 '17 at 0:34
  • 1
    $\begingroup$ Denote the symmetric/antisymmetric combinations by $$ \delta^{\pm}_{ij,n+1}=x_{i,n}\pm x_{j,n} $$ where $x_i\in \{a,b,c\}$ and $i\neq j$ then $$ \delta^{+}_{ij,n+1}\delta^{-}_{ij,n+1}=(\delta^+_{ij,n})^2((\delta_{ik,n}^+)^2-(\delta_{jk,n}^+)^2)=(\delta^+_{ij,n})^2(\delta^-_{ij,n})^2 $$ which means that the problem can be reduced to $$ 4(a_{n+1}^2-b^2_{n+1})=a_{n}^2-b^2_{n}\\ 4(a_{n+1}^2-c^2_{n+1})=a_{n}^2-c^2_{n}\\ 4(c_{n+1}^2-b^2_{n+1})=c_{n}^2-b^2_{n} $$ $\endgroup$ – tired Jan 24 '17 at 1:07
  • $\begingroup$ assume furthermore $i>j$ because there is no distiniction between $a-b$ and $b-a$ etc. The problem seems to be quite manageable now $\endgroup$ – tired Jan 24 '17 at 1:36

Here is an observation: As in your link, if $b_0 = c_0$ then we can prove recursively that $b_n = c_n$ for all $n \geq 0$. Then plugging this to OP's recurrence relation, we find that the sequence $(a_n, b_n)$ satisfies the Schwab-Borchardt recurrence relation

$$ a_{n+1} = \frac{a_n + b_n}{2}, \qquad b_{n+1} = \sqrt{a_{n+1}b_n}. $$

So if we write $(a_0, b_0) = (a, b)$, then the limit is given by the Schwab-Borchardt mean

$$ \lim_{n\to\infty} a_n = \lim_{n\to\infty} b_n = SB(a_0, b_0) = \begin{cases} \dfrac{\sqrt{a^2 - b^2}}{\operatorname{arccosh}(a/b)}, & a > b \\ \dfrac{\sqrt{b^2 - a^2}}{\operatorname{arccos}(a/b)}, & a < b \\ a, & a = b \end{cases} \tag{*} $$

Anyway, let me write down my failed attempt to mimic Carlson's proof of $\text{(*)}$ so that future me do not repeat this mistake.

Define $I(a,b,c)$ by

$$ I(a,b,c) := \lim_{R\to\infty} \int_{-R}^{R} \frac{dx}{(x+a^2)^{1/3}(x+b^2)^{1/3}(x+c^2)^{1/3}}, $$

where $z^{1/3} = \exp(\frac{1}{3}\log z)$ with the branch cut $-\pi < \arg(z) \leq \pi$. Then we can check that $I(a, b, c)$ converges. Now using the substitution $x \mapsto 4x + ab + bc + ca$, we find that

$$ I(a, b, c) = I\left( \frac{\sqrt{(a+b)(a+c)}}{2}, \frac{\sqrt{(b+c)(b+a)}}{2}, \frac{\sqrt{(c+a)(c+b)}}{2} \right). $$

This tells us that $I(a_n,b_n,c_n) = \cdots = I(a_0,b_0,c_0)$. If we recall how the AGM is computed from Landen's transformation, this may possibly allow us to analyze $L$ using $I$.

Well, it turns out that the function $I$ has a serious issue, which is that $I$ is identically zero! This can be checked either by using the fact $I(a,a,a) = 0$ or by interpreting $I(a,b,c)$ as a value of the Schwarz–Christoffel mapping.

  • $\begingroup$ Very nice! I didn't know this particular class of means... $\endgroup$ – tired Jan 24 '17 at 1:40
  • $\begingroup$ @tired, I was also surprised that this has closed form, considering that AGM involves elliptic functions. $\endgroup$ – Sangchul Lee Jan 24 '17 at 1:58
  • $\begingroup$ @SangchulLee, but the sequence you gave is the same as in this answer, even though the sequences in the OP are different. Ah, I see, they are actually the same... $\endgroup$ – Yuriy S Jan 24 '17 at 12:50
  • $\begingroup$ @YuriyS, Assuming $b_0 = c_0$, you can prove recursively that $b_n = c_n$ for all $n \geq 0$ and that your recurrence relation reduces to what I wrote down. For instance, $$ a_{n+1} = \frac{\sqrt{(a_n + b_n)(a_n + b_n)}}{2} = \frac{a_n + b_n}{2} $$ and similarly $$ b_{n+1} = \sqrt{\frac{(b_n + a_n)(b_n + b_n)}{4}} = \sqrt{\frac{a_n+b_n}{2} \cdot b_n} = \sqrt{a_{n+1}b_n}. $$ $\endgroup$ – Sangchul Lee Jan 24 '17 at 12:54
  • 1
    $\begingroup$ @SangchulLee, I've read you edit and it's great - you regonized the Carlson's transformation. I'll make an addition to the OP. $\endgroup$ – Yuriy S Jan 25 '17 at 8:49

I can show that the sum of the squares of the terms decreases at each step.

I think this implies convergence, but I am not completely sure.

$a_{n+1} =\frac{\sqrt{(a_n+b_n)(a_n+c_n)}}{2} \\ b_{n+1}= \frac{\sqrt{(b_n+a_n)(b_n+c_n)}}{2} \\ c_{n+1} =\frac{\sqrt{(c_n+a_n)(c_n+b_n)}}{2} $

I'm going to play around and see if anything interesting happens, with a goal of proving convergence, maybe.

Multiplying, we get

$a_{n+1}b_{n+1}c_{n+1} =(a_n+b_n)(a_n+c_n)(b_n+c_n)/8 =(a^2 b + a^2 c + a b^2 + 2 a b c + a c^2 + b^2 c + b c^2)/8 $ (omitting the "_n") so that

$\begin{array}\\ \dfrac{a_{n+1}b_{n+1}c_{n+1}}{abc} &=(\frac{a}{c} + \frac{a}{b} + \frac{b}{c} + 2 + \frac{c}{b} + \frac{b}{a} + \frac{c}{a})/8\\ &=(\frac{a}{c} + \frac{c}{a} + \frac{a}{b} + \frac{b}{a} + \frac{b}{c}+ \frac{c}{b} + 2 )/8\\ &=(\frac{a}{c} -2+ \frac{c}{a} + \frac{a}{b}-2 + \frac{b}{a} + \frac{b}{c}-2+ \frac{c}{b} + 8 )/8\\ &=(g(\dfrac{a}{c}) + g(\dfrac{a}{b}) + g(\dfrac{b}{c}))/8+1 \qquad\text{where } g(x) = (\sqrt{x}-\dfrac1{\sqrt{x}})^2=x+\dfrac1{x}-2\\ \end{array} $

Note that $g'(x) =1-\dfrac1{x^2} $.

Don't know what to do with this, so I'll try something else.

$\begin{array}\\ a_{n+1}-a &=\frac{\sqrt{(a+b)(a+c)}}{2}-a\\ &=a(\frac{\sqrt{(1+b/a)(1+c/a)}}{2}-1)\\ \end{array} $

Again nothing.

Let's try this.

Since $(a+b+c)^2 \le 3(a^2+b^2+c^2) $ with equality iff $a=b=c$,

$\begin{array}\\ a_{n+1}^2+b_{n+1}^2+c_{n+1}^2 &=((a+b)(a+c)+(a+b)(b+c)+(a+c)(b+c))/4\\ &=(a^2+ab+ac+bc+ab+ac+b^2+bc+ab+ac+bc+c^2)/4\\ &=(a^2+b^2+c^2+3ab+3ac+3bc)/4\\ &=(\frac32(a^2+b^2+c^2+2ab+2ac+2bc)-\frac12(a^2+b^2+c^2))/4\\ &=(\frac32(a+b+c)^2-\frac12(a^2+b^2+c^2))/4\\ &\le(\frac32 3(a^2+b^2+c^2)-\frac12(a^2+b^2+c^2))/4\\ &=a^2+b^2+c^2\\ \end{array} $

Therefore, if at least two of $a, b, c$ are distinct, the sum of their squares decreases.

This is not a proof of convergence, but a start.

Let's try a variation on this last result.

$\begin{array}\\ a_{n+1}^2+b_{n+1}^2+c_{n+1}^2 &=((a+b)(a+c)+(a+b)(b+c)+(a+c)(b+c))/4\\ &=(a^2+ab+ac+bc+ab+ac+b^2+bc+ab+ac+bc+c^2)/4\\ &=(a^2+b^2+c^2+3ab+3ac+3bc)/4\\ \end{array} $


$\begin{array}\\ a_{n+1}^2+b_{n+1}^2+c_{n+1}^2 -(a^2+b^2+c^2) &=(-3a^2-3b^2-3c^2+3ab+3ac+3bc)/4\\ &=-3(a^2+b^2+c^2-ab-ac-bc)/4\\ &=-3(2a^2+2b^2+2c^2-2ab-2ac-2bc)/8\\ &=-3((a-b)^2+(a-c)^2+(b-c)^2)/8\\ \end{array} $

This shows precisely how the sum of squares decreases at each step.

I think that this implies convergence.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.